International Year of Rangelands and Pastoralists 2026 - Velasco, G. (Food and Agriculture Organization of the United Nations, 2025)
A presentation made by the a representative from the FAO convened Secretariat of the International Year of Rangelands and Pastoralists on the year. The presentation was made at a webinar organised by the CGIAR Science Program on Multifunctional Landscapes to raise awareness about the year amongst the CGIAR.